2022
DOI: 10.1155/2022/5299497
|View full text |Cite|
|
Sign up to set email alerts
|

Physical Education Teaching Strategy under Internet of Things Data Computing Intelligence Analysis

Abstract: Racket sports such as tennis are amongst the most popular recreational sports activities. Optimizing tennis teaching methods and improving teaching modes can effectively improve the teaching quality of tennis. In this study, a video and image action recognition system based on image processing techniques and Internet of things is developed to overcome the shortcomings of the traditional tennis teaching methods. To validate its performance, the students of tennis courses are divided into experimental group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Schools should firmly establish a holistic view of education and teaching and play a key role in promoting the construction of sports teaching and practicing course ideology to ensure that the process of sports teaching and practicing course ideology is scientific, systematic and effective and to find and solve the problems of sports teaching and practicing course ideology in a timely manner [25][26]. The relevant leading departments of the school should consciously and actively communicate the policy so as to achieve consistency in the pace between departments.…”
Section: Increase the Implementation Of The Integration Of Physical E...mentioning
confidence: 99%
“…Schools should firmly establish a holistic view of education and teaching and play a key role in promoting the construction of sports teaching and practicing course ideology to ensure that the process of sports teaching and practicing course ideology is scientific, systematic and effective and to find and solve the problems of sports teaching and practicing course ideology in a timely manner [25][26]. The relevant leading departments of the school should consciously and actively communicate the policy so as to achieve consistency in the pace between departments.…”
Section: Increase the Implementation Of The Integration Of Physical E...mentioning
confidence: 99%
“…There plenty of top tennis players. As a result, tennis training for young people is a top precedence, country is starting to take notice [7,8]. This has allowed for more indepth youth tennis training, as well as the winning of numerous struggles, opportunities for young tennis players [9].Yang developed volleyball fitness method depend on data mining, analyzed five major components of volleyball players using mathematical statistics, generated volleyball typical indicators depend on five fitness traits [10].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%